STRATEGI TIM REDAKSI LINGKAR KREATIF NET TV SULAWESI SELATAN DALAM MENARIK MINAT PENONTON (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This study aims to determine the strategy of the editorial team for the South Sulawesi NETTV Creative Lingkar program in attracting audience interest and to find out the supportingand inhibiting factors in the production process of the South Sulawesi NET TV CreativeLingkar program. This type of research uses descriptive research methods that provide an overview offactual conditions that reveal certain social situations by describing reality correctly, and bydigging up information from sources by collecting and analyzing relevant data fromnatural situations. The results of this study indicate that the strategy that has been carried out by the editorial team of the Lingkar Kreatif program is in attracting the interest of the audience so that theaudience has an interest in what is shown or presented. Namely applying three basic concepts, namely: (1) sharing information related to the world of education, (2) sharing information related to arts and culture, and (3) sharing information related to the world of entertainment. In addition, in its implementation, the South Sulawesi NET TV Creative Circle program also applies strategies, namely: (a) pre-production which includes: editorial meetings, determining themes/topics, and mastery of the material by hosts/voice actors. (b) production, which includes: leading and briefing, to stage (c) post-production: evaluation, making daily by-minute shares and ratings, and assisting in the editing process. The supporting factors in the production process of the South Sulawesi NET TV Creative Circle program include (1) production equipment, and (2) transmitter locations at several points. While the inhibiting factors include: (1) schedule changes, and (2) the crew is experiencing problems.